A study of bioethanol fuel characteristics in the combustion chamber of gasoline engine using magnetization technology - Ulfiana, Andi; Nufus, Tatun Hayatun; Ridwan, Emir; Ekayuliana, Arifia; Abadi, Cecep Slamet; Apriana, Asep; Susanto, Iwan (Eastern-European Journal of Enterprise Technologies, 2021)
Bioethanol is a renewable energy that can replace gasoline, which will run out in the future. This study investigates the influence of magnetization of bioethanol fuel on the fuel combustion temperature in the combustion chamber of a gasoline motor. The fuel used is bioethanol with a composition of E0 (pure gasoline), E10 (10 % bioethanol+90 % gasoline), E20 (20 % bioethanol+80 % gasoline), E30 (30 % bioethanol+70 % gasoline), E40 (40 % bioethanol+60 % gasoline). The fuel passed through the magnet with a magnetic variation of 647.15 Gauss, 847.25 Gauss, 1419.57 Gauss. The temperature sensor used is a K-type thermocouple. The temperature sensor was inserted in the combustion chamber to measure the combustion chamber temperature. The thermocouple data were recorded in Microsoft Excel on a computer using the LabVIEW program via NI-USB 9213 interface. The temperature data recorded is 400 data/second. The results obtained without exposure to the magnetic field, the lowest peak temperature of 577.1998 °C at E40 and the highest peak temperature of 582.1786 °C at E0. The higher the bioethanol content, the lower the temperature of fuel combustion to the low bioethanol viscosity. The increasing magnetic field strength will increase the combustion temperature; hence the fuel burned quickly and the combustion process is more perfect. The result obtained with the magnetic field exposure, the lowest peak temperature of 577.8347 °C is at E40. The highest peak temperature of 587.36 °C is at E0. The use of a magnetic field in the bioethanol fuel mixture can increase the combustion temperature so that the fuel molecules move freely and the fuel is more easily mixed with oxygen. As more fuel is burned, the combustion of the fuel becomes complete